Development and evaluation of a case-based digital learning tool about children's mathematical thinking for elementary school teachers (L-TEST) - Olkun, Sinan; Altun, Arif; Deryakulu, Deniz (European journal of teacher education, 2009)
It is important for teachers of mathematics to know how pupils react to certain mathematical situations and what these reactions imply, in order to design more effective instructional environments based on their learning needs. This study reports the development processes of a digital learning tool (Learning Tool for Elementary School Teachers (L-TEST)) that shows children's mathematical thinking for the ages of 4-11 years across certain problem situations. L-TEST is designed as a support tool to be used in teacher education. A case-based instructional model was used in designing the instructional tool. Video recordings were digitised to provide a rich environment where learners observe exemplary cases. These exemplified videos included children's mathematical development in the subjects of numbers and shapes, combined with discussions in line with the current research findings. Finally, a usability test for the learning tool was carried out.